The Territorial Growth Pole Model as a System of Development Factors on the Example of Poland - Elżbieta Wojnicka-Sycz (Barometr Regionalny, 2013)
Growth pole strategies have been undertaken in the world since the 1960s with mixed results. In the article a complex approach to this phenomenon is proposed and tested for Poland. The territorial growth pole is considered to be based on a system of developmental factors forming natural, financial, physical, intellectual, socio-economic and administrative types of capital that create suitable conditions for location of innovative branches and the positive externalities connected with them. Areas affluent in developmental factors forming the above forms of capital have the best results both in terms of GDP dynamics and its level.